Investigating 2-hydroxypropyl-β-cyclodextrin (HPβCD) as a novel therapeutic agent for breast cancer - Saha, Sourav Taru (University of the Witwatersrand, Johannesburg, 2019)
Cancer cells have an increased need for cholesterol, which is required for cell membrane integrity. Cholesterol accumulation has been described in various malignancies including breast cancer. Cholesterol has also been known to be the precursor of estrogen and vitamin D, both of which play a key role in the histology of breast cancer. Elevated cholesterol levels have been linked to breast cancer therefore depleting cholesterol levels in cancer cells can be a viable strategy for treatment. 2-hydroxypropyl-β-cyclodextrin (HPβCD) is a cholesterol depleting compound which is a cyclic amylose oligomer composed of glucose units. It solubilizes cholesterol and is proven to be toxicologically benign in humans. This led us to hypothesise that it might deplete cholesterol from cancer cells and may prove to be a clinically useful compound. Our work provides experimental evidences to support this hypothesis. We identified the potency of HPβCD in vitro against two breast cancer cell lines: MCF7 (Estrogen positive, ER+), MDA-MB-231 [Triple negative breast cancer (TNBC)], and compared the results against two normal cell lines: MRC-5 (Normal Human Lung Fibroblasts) and HEK-293 (Human embryonic kidney) using cytotoxic, apoptosis and cholesterol based assays. HPβCD treatment reduced intracellular cholesterol resulting in significant breast cancer cell growth inhibition through apoptosis. The results hold true for both ER+ and TNBC. We have also tested HPβCD in vivo in MF-1 mice xenograft model and obtained 73.9%, 94% and 100% reduction in tumour size for late, intermediate and early stage TNBC. These data suggest that HPβCD can prevent cholesterol accumulation in breast cancer cells and is a promising anti- cancer agent
Thesis Submitted in fulfillment of the requirements for the degree Philosophiae Doctor (PhD.) in Molecular and Cell Biology in the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, South Africa 2019
Keywords: Cancer cells; Cholestero; 2-hydroxypropyl-β-cyclodextrin (HPβCD); Breast cancer; SDG-3: Good health and well-being